When Trouble Comes: A Christian View of Evil, Sin and Suffering. - Sellers, James E. (New York ABINGDON PRESS, 1946)
Some people feel that God causes human suffering or that, at the very least, he is indifferent to it. But is that what the Bible teaches? You might be surprised at the answer.
Keywords: Education